EFEK PENAMBAHAN EVAPORATOR PADA ATMOSPHERE WATER HARVESTER (AWH) TERHADAP PERFORMA SISTEM - Juli Mrihardjono; Didik Ariwibowo; Sutrisno Sutrisno; Dista Yoel Tadeus (Gema Teknologi, 2021)
Atmosphere Water Harvester (AWH) was investigated to get water collected from air in elevated performance. Improvement was performed by introducing a series-arrangement of two evaporators. Air flew through the evaporators in cross-flow. This arrangement would influence performance of the AWH system in title of COP, MHI, and specific energy consumption. The AWH was designed using vapor compression refrigeration system. Parameter measured to the system were refrigerant temperature in suction and discharge line, inlet and outlet pipe wall temperatures at evaporator and condenser, air velocity enter into evaporator, and electrical energy consumption. Instrument used in this research were refrigerant pressure-temperature gauge, K-type digital thermometer, digital fan anemometer, thermo-hygro meter, and kWh meter. Air temperature and RH data were 36,5 oC, 40%, and 19 oC, 42 %  for inlet and outlet air stram at evaporator, subsequently. With air velocity 1.5 m/s, the COP of the system was 3.7. Water collected  from AWH was 1.1 litres/hour with energy consumption of 1.24 kWh. The AWH could be considered as a water harvester with value of specific energy of 1.13 kWh/litre and MHI of 0,2.